A novel hybrid BCI speller based on RSVP and SSVEP paradigm. (April 2020) - Jalilpour, Shayan; Hajipour Sardouie, Sepideh; Mijani, Amirmohammad
Highlights: A new hybrid paradigm is proposed in this paper for spelling characters by brain signals; this paradigm is a RSVP speller, which is combined with SSVEP stimulation. In this system, character selection is performed in two parallel steps. The target group is selected by P300 stimuli, and the target character is chosen by SSVEP stimuli. The performance of the system, including character detection accuracy and information transfer rate (ITR), is significantly enhanced as compared with previous RSVP spellers. Abstract: Background and objective: Steady-state visual evoked potential (SSVEP) and rapid serial visual presentation (RSVP) are useful methods in the brain-computer interface (BCI) systems. Hybrid BCI systems that combine these two approaches can enhance the proficiency of the P300 spellers. Methods: In this study, a new hybrid RSVP/SSVEP BCI is proposed to increase the classification accuracy and information transfer rate (ITR) as compared with the other RSVP speller paradigms. In this paradigm, RSVP (eliciting a P300 response) and SSVEP stimulations are presented in such a way that the target group of characters is identified by RSVP stimuli, and the target character is recognized by SSVEP stimuli. Results: The proposed paradigm achieved accuracy of 93.06%, and ITR of 23.41 bit/min averaged across six subjects. Conclusions: The new hybrid system demonstrates that by using SSVEP stimulation in Triple RSVP speller paradigm, we could enhance the performance of the system as compared with the traditional Triple RSVP paradigm. Our work is the first hybrid paradigm in RSVP spellers that could obtain the higher classification accuracy and information transfer rate in comparison with the previous RSVP spellers.